The Effect Of Career Development And Work Culture On Job Satisfaction - Sudiarti, Sri; Edward, Yusuf Ronny; Suryani; Sundarsih, Dedeh; Hartanto (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2025)
This study aims to determine the influence of career development and work culture on job satisfaction at PT. Surya Dharma Utama (SDU) Semarang. The research method used is quantitative. The sample size was 58 employees at PT. Surya Dharma Utama (SDU) Semarang. The sample size was determined using a saturated/census sample. The research instruments used were a questionnaire and an interview schedule. The results of the quantitative study were analyzed using SPSS 26. The results showed that career development and work culture have a positive and significant effect on job satisfaction at PT. Surya Dharma Utama (SDU) Semarang.